y – 3)/4 + (y – 1)/5 – (y – 2)/3 = 1
(3x – 2)/3 + (2x + 3)/3 = (x + 7)/6
(8y – 5)/(7y + 1) = -4/5
(5 – 7y)/(2 + 4y) = -8/7. Solve these linear equations..
Answers
Answered by
0
Answer:
(
4
3(y−5)
)−4y=3−(
2
(y−3)
)
3(y−5)−16y=12−2(y−3)
3y−15−16y=12−2y+6
3y−16y+2y=12+6+15
−11y=33
∴y=−3
Step-by-step explanation:
2.
(3x-2)/3+(2x+3)/3=x+7/6
We move all terms to the left:
(3x-2)/3+(2x+3)/3-(x+7/6)=0
We add all the numbers together, and all the variables
(3x-2)/3+(2x+3)/3-(+x+7/6)=0
We get rid of parentheses
(3x-2)/3+(2x+3)/3-x-7/6=0
We calculate fractions
There is no solution for this equation
Similar questions